GERAKAN PROTES SOSIAL PETANI DI JAWA PADA MASA KOLONIAL (DALAM PERSPEKTIF SEJARAH SOSIAL PEDESAAN) - Muntholib, Abdul (Forum Ilmu Sosial, 2009)
Movements of social politics protest in all its forms is not a new thing in the history of Indonesia. Social protest movement of farmers in Java does not belong to the past history, but a historical phenomenon that is always present in every period of time, both in the past, present, and future. It should be always to question whether the factors that cause social protest Javanese rural farmers who can be seen in terms of economic, political, and social in the social history of rural perspective in Java.Keywords: Social protest movements, social history, farmers in Java